Birefringent dispersive FDTD subgridding scheme. Issue 17 (1st August 2016) - De Deckere, B.; Van Londersele, A.; De Zutter, D.; Vande Ginste, D.
Abstract : A novel 2D finite difference time domain (FDTD) subgridding method is proposed, only subject to the Courant limit of the coarse grid. By making μ or ε inside the subgrid dispersive, unconditional stability is induced at the cost of a sparse, implicit set of update equations. By only adding dispersion along preferential directions, it is possible to dramatically reduce the rank of the matrix equation that needs to be solved.